Immediate Sequential Bilateral Cataract Surgery: Opinions among Refractive Surgeons in the United States and a Comparative Analysis with European Consultants - Sloan W. Rush; Andres E. Guerrero Criado; Guy M. Kezirian; Daniel Durrie (Journal of Ophthalmology)
Purpose. To analyze the perspectives of practicing refractive surgeons regarding the implementation of Immediate Sequential Bilateral Cataract Surgery (ISBCS) in the United States (US) and to compare their perspectives with those of European colleagues. Setting. Online refractive surgery forum. Design. A survey-based questionnaire. Methods. An electronic survey was emailed to all surgeon members of the Refractive Surgery Alliance (RSA) in the US. Participants were prompted to score their impressions regarding various aspects regarding ISBCS. Responses were compared to published reports conducted among European surgeons. Results. The electronic link to the survey was emailed to US-based surgeon members of the RSA, where 107 participated (44.6%). Twenty-seven (25.2%) reported that they currently perform ISBCS. Twenty-three (22.5%) of the respondents indicated they felt ISCBCS should be offered as a standard of care for routine cataract surgery. For surgeons that do not perform ISBCS, the most important factors were related to medicolegal issues and decreased reimbursement, whereas evidence of effectiveness and complications related to ISBCS were less important. Compared to practitioners abroad, 67.2% of European ophthalmic surgeons, compared to 25.2% of US surgeons, perform ISBCS (p<0.0001). Conclusions. While US refractive surgeons often perform bilateral corneal procedures, many significant barriers exist to the widespread adoption of ISBCS. Concerns reported by US surgeons mirror those reported by surgeons in Europe. The majority of the US refractive surgeons in this survey indicate that ISBCS should not be the standard of care in routine cases, with the prevailing reason being concerns about decreased physician reimbursement and potential medicolegal issues, not safety.